Physical activity and depression: a large cross‐sectional, population‐based study across 36 low‐ and middle‐income countries. (5th October 2016) - Stubbs, B.; Koyanagi, A.; Schuch, F. B.; Firth, J.; Rosenbaum, S.; Veronese, N.; Solmi, M.; Mugisha, J.; Vancampfort, D.
Abstract : Objective: Physical activity (PA) is good for health, yet several small‐scale studies have suggested that depression is associated with low PA. A paucity of nationally representative studies investigating this relationship exists, particularly in low‐ and middle‐income countries (LMICs). This study explored the global association of PA with depression and its mediating factors. Method: Participants from 36 LMICs from the World Health Survey were included. Multivariable logistic regression analyses were undertaken exploring the relationship between PA and depression. Results: Across 178 867 people (mean ± SD age = 36.2 ± 13.5 years; 49.9% male), the prevalence of depression and the prevalence of low PA were 6.6% and 16.8% respectively. The prevalence of low PA was significantly higher among those with depression vs. no depression (26.0% vs. 15.8%, P < 0.0001). In the adjusted model, depression was associated with higher odds for low PA (OR = 1.42; 95% CI = 1.24–1.63). Mediation analyses demonstrated that low PA among people with depression was explained by mobility limitations (40.3%), pain and discomfort (35.8%), disruptions in sleep and energy (25.2%), cognition (19.4%) and vision (10.9%). Conclusion: Individuals with depression engage in lower levels of PA in LMICs. Future longitudinal research is warranted to better understand the relationships observed.